Observation-to-Imitate Plus Practice Could Add Little to Physical Therapy Benefits Within 31 Days of Stroke: Translational Randomized Controlled Trial. (February 2013) - Cowles, Tracy; Clark, Allan; Mares, Kathryn; Peryer, Guy; Stuck, Rebecca; Pomeroy, Valerie
Background and Purpose . Observation of action with intention-to-imitate (OTI) might enhance motor recovery. This early phase trial investigated whether OTI followed by physical practice (OTI + PP) enhanced the benefits of conventional physical therapy (CPT) on upper limb recovery early after stroke. Methods . Participants were 3 to 31 days poststroke. They had substantial paresis and ability to imitate action with their ipsilesional arm. After baseline measures, participants were randomized to either OTI + PP in addition to CPT or to CPT only. Outcome measures were made after 15 days of treatment. The measurement battery was the Motricity Index (MI) and the Action Research Arm Test (ARAT). Change, baseline to outcome, was examined using the Wilcoxon test for within group and Mann–Whitney U test for between groups. Results . Sixty-five of 570 stroke survivors were eligible, 55 were able to imitate, 37 gave informed consent, 7 were transferred out of area before baseline, and 29 were randomized. Outcome measures were completed with 13 CPT participants and 9 OTI + PP participants. Both groups showed statistically significant improvements for the MI (CPT median change 8, P = .003; OTI + PP median change 10, P = .012) but the median (95% confidence interval [CI]) between-group difference was 0.0 (−11, 16), P = 1.000. For the ARAT, only the CPT group showed a statistically significant improvement (median 9, P = .006). The median (95% CI) between-group difference of 1.0 (−18, 23) was not statistically significant ( P = .815). Conclusions . These findings suggest that OTI + PP might add little to the benefits of CPT early after stroke.